Academic Research on cattle’s acclimatisation process. - Silva, Flavio (2019)
ACADEMIC RESEARCH ON CATTLE’S ACCLIMATISATION PROCESS Flávio Silva1, Cristina Conceição1,2, Liliana Cachucho3, Catarina Matos1, Ana Lúcia Garrido1, Ana Geraldo1,2, Elsa Lamy2, Fernando Capela e Silva2,4, Paulo Infante5 & Alfredo Pereira1,2, 1Departamento de Zootecnia, Universidade de Évora, Portugal; 2ICAAM, Universidade de Évora, Portugal; 3CEBAL, Beja, Portugal; 4Departamento de Biologia, Universidade de Évora, Portugal; 5Deparatamento de Matemática, Universidade de Évora, Portugal. ABSTRACT Animal’s welfare and performance is compromised by environmental heat stress, present during summer in the Mediterranean climate. Heat stress effects are well known and widely studied, although the mechanisms of season acclimatisation are less well understood. Throughout the last 20 years, we have been studying this process in the Mediterranean and tropical regions, aiming to understand it better, developing and improving methodologies and search for reliable biomarkers of thermal stress. The climatic changes, the more frequent extreme events and the increase of ambient temperature at the surface of the earth were identified as a problem to the animals in general and particularly under production systems conditions. Then, the main question is how those factors can affect the farm animals, especially those with higher genetic merit for production and lack of environmental adaptation. With these premises, were developed research projects on cattle’s acclimatisation process. These projects outcomes were: 2 PhD thesis and 5 Master dissertations, alongside ten articles peer-review and index journals and 20 publications in the book of abstracts and also several communications in national and international symposiums. Keywords: acclimatisation; heat stress; cattle.